Analisis Fundamental Saham Terhadap Pertumbuhan Perusahaan STUDI KASUS PADA PT. HOLCIM INDONESIA, TBK. - Marpaung, Annaria Magdalena (Jurnal Ilmiah Manajemen Kesatuan, 2013)
Fundamental analysis is a method of analysis using the fundamental strength of a country. In general, the fundamental strength of a country is shown by the country’s economic data. Fundamental analysis states that every stock has an intrinsic value. This analysis attempts to calculate the intrinsic value of a stock by using the fundamental data of the “ Company’s Financial Statements “, such as earning devidends, sales, capital structure, risk etc. This analysis will compare the intrinsic value with the market value to determine whether the market price of shares has reflected its intrinsic value or has not. The purpose of this study is to find out the company’s fundamental analysis with the liquidity ratio, the company’s growth, and the impact of the analysis on the company’s growth. The result of the research indicates that the two public companies analyzed for six years in terms of cash and cash equivalents, inventories, current assets and current liabilities is that PT. Holcim Indonesia, Tbk was stable. Concerning profit growth, PT. Holcim Indonesia, Tbk yielded profit. The analysis of those factors shows that it has positive effect for PT. Holcim Indonesia, Tbk which causes many investors will invest their funds. Keywords : Fundamental analysis; liquidity ratio; company’s growth